Depicting the cellular complexity of pancreatic adenocarcinoma by Imaging Mass Cytometry: focus on cancer-associated fibroblasts - Erreni, Marco; Fumagalli, Maria Rita; D’Anna, Raffaella; Sollai, Mauro; Bozzarelli, Silvia; Nappo, Gennaro; Zanini, Damiano; Parente, Raffaella; Garlanda, Cecilia; Rimassa, Lorenza; Terracciano, Luigi Maria; Biswas, Subhra K.; et al. (Frontiers in Immunology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) represents the complexity of interaction between cancer and cells of the tumor microenvironment (TME). Immune cells affect tumor cell behaviour, thus driving cancer progression. Cancer-associated fibroblasts (CAFs) are responsible of the desmoplastic and fibrotic reaction by regulating deposition and remodelling of extracellular matrix (ECM). As tumor-promoting cells abundant in PDAC ECM, CAFs represent promising targets for novel anticancer interventions. However, relevant clinical trials are hampered by the lack of specific markers and elusive differences among CAF subtypes. Indeed, while single-cell transcriptomic analyses have provided important information on the cellular constituents of PDACs and related molecular pathways, studies based on the identification of protein markers in tissues aimed at identifying CAF subtypes and new molecular targets result incomplete. Herein, we applied Multiplexed Imaging Mass Cytometry (IMC) at single-cell resolution on 8 human PDAC tissues to depict the PDAC composing cells, and profiling immune cells, endothelial cells (EC), as well as endocrine cells and tumour cells. We focused on CAFs by characterising up to 19 clusters distinguished by phenotype, spatiality, and interaction with immune and tumor cells. We report evidence that specific subtypes of CAFs (CAFs10 and 11) predominantly enriched the tumour-stroma interface region and closely associated with tumour cells. CAFs expressing different combinations of FAP, podoplanin and cadherin-11, were associated with a higher level of CA19-9. Moreover, we identified specific subsets of FAP+ and podoplanin+/cadherin-11+ CAFs enriched in patients with negative prognosis. The present study provides new general insights into the complexity of the PDAC microenvironment by defining phenotypic heterogeneities and spatial distributions of CAFs, thus suggesting different functions of their subtypes in the PDAC microenvironment.